2020
DOI: 10.1159/000508755
|View full text |Cite
|
Sign up to set email alerts
|

Current Role of Multiparametric MRI and MRI Targeted Biopsies for Prostate Cancer Diagnosis in Germany: A Nationwide Survey

Abstract: Introduction: Multiparametric MRI (mpMRI) and MRI targeted biopsies (MRtb) are a new standard in prostate cancer (PCa) screening and diagnosis. Guidelines already include this approach for patients at risk. We aimed to gather information from German urologists about their knowledge, routine use, and attitude toward mpMRI and consecutive biopsy methods. Materials and Methods: An anonymous online questionnaire was sent via Survey Monkey to the members of the German Society of Urology (DGU). Statistical analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Recently, several diagnostic procedures, such as multiparametric magnetic resonance imaging (mpMRI) or prostate health index, have become available to increase the prediction of IPC [20, 21]. On the other hand, it has so far been difficult to anticipate the occurrence of IPC after surgical treatment of BPO.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Recently, several diagnostic procedures, such as multiparametric magnetic resonance imaging (mpMRI) or prostate health index, have become available to increase the prediction of IPC [20, 21]. On the other hand, it has so far been difficult to anticipate the occurrence of IPC after surgical treatment of BPO.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Goel et al found that upgrading rates are significantly higher in SB Gleason patterns, while concordance is significantly more frequent in TB Gleason patterns. These observations are particularly important since MRI-targeted biopsies are increasing within recent years due to improving quality, as well as easy and quick performance [ 28 , 29 , 30 , 31 ]. In consequence, whenever TB is performed and separate biopsy GS are available for TB and SB, clinical decision-making and patient counseling should rather be based on the findings of TB GS than on SB GS for predicting final pathology.…”
Section: Discussionmentioning
confidence: 99%
“…A recent nationwide survey among clinicians in Germany underscores the widespread acceptance of mpMRI and targeted prostatic biopsies [5]. Despite the gain in diagnostic accuracy by mpMRI, there is still an on-going effort to utilize this information for risk classification.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that it is possible to enhance the prediction of PCa detection by adding serum miRNA expression levels to clinical data and the PI-RADS score. However, up to now, there is a strong suggestion that PI-RADS 3 lesions should also be biopsied [5,23], because they might harbor significant PCa ranging from 12% [24] to 34% in current cohorts [25], even though other studies show only a limited incidence of significant PCa [26]. Yang et al utilized mpMRI imaging information and routine clinical parameters for modeling cancer risk particularly in patients with PI-RADS 3 lesions and suggested their model for the reduction of unnecessary biopsies [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation